The Influence of Islamic Branding, Maslahah Perception, and Religiosity on Halal Product Purchase Decisions through Purchase Intention - Hidayatullah, Fakaruzzaman (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to determine the role of Islamic law in young Muslim consumers in consuming halal products. Growing technology has positive and negative impacts on the lives of Muslims, especially the younger generation, the intermingling of materialism, hedonism and utilitarianism culture in the younger generation has an impact on changing behavior as Muslims, especially in consumption behavior according to Islamic law, a preliminary survey of researchers to Muslim consumers The young generation in East Java shows that consumptive behavior in purchasing products without finding out the type of product consumed in terms of Islamic law, but rather as a basis for meeting the needs of life. The results found that Islamic branding, perceptions maslahah and religiosity have a very strong influence on buying interest and purchasing decisions for halal products. Purchase interest mediates the influence of Islamic branding, perceptions of maslahah and religiosity on the decision to purchase halal products. Empirically the results of this study indicate that Islamic law has an important role in regulating the behavior of young Muslim consumers in the State Islamic Religious College students in East Java in purchasing halal products